A TRANSLATION ANALYSIS OFINDONESIAN LAW OF INVESTMENT AND LAW OF MINERAL & COAL MINING:A CASE STUDY OF CULTURAL WORDS FOCUSED ON SOCIAL-POLITICAL AND ADMINISTRATIVE JARGONS WRITTEN IN INDONESIAN LEGAL DOCUMENTS - Rd Riana Gustafa, - (2010)
This paper is entitled A translation analysis of Indonesian Law of Investment and Law of Mineral and Coal mining. The study focused on three research questions. They were: 1) what social-political and administrative jargons are commonly found in the translated book of Indonesian Mineral & Coal mining and Law of investment by SuyudMargono& Associates? 2) Which procedures are commonly used by the translator in translating the cultural terms on social-political and administrative jargons in the translated book of Indonesian Law of Mineral & Coal mining and Law of investment by SuyudMargono& Associates?3) How is the quality of the translation? In accordance with the problem of the study, a descriptive method was applied and the collected data were organized and analyzed as qualitative data. The findings showed that legal category was the most frequently used type of cultural words on social-political and administrative jargons found in the book (56.63%), followed by administrative category (24.70%), social category (9.64%), political category (8.43%), and the last religious category (0.60%). In addition, there were 16 procedures used in translating those jargons, the most commonly used procedure is Shifts or transposition procedure (29.52%). Finally, based on the translation assessment by the two judges,this study showed that the quality of translation on the translated book of Indonesian Mineral & Coal mining and Law of investment by Suyud Margono& Associates which was viewed from three aspects (accuracy, clarity, and naturalness) is categorized as "excellent". Thus, It can be concluded that the translations accurate, clear, has nothing omission, addition or any changes of meaning.